(untitled) (Prithvi Academic Journal, 2024)
This paper explored the incorporation of entrepreneurial content in the industrial design curriculum in universities in Southwest Nigeria, with a specific focus on textile design. Acknowledging the landscape of the global textile industry and the cultural significance of textiles in Southwest Nigeria, the study examined the existing industrial design curriculum, highlighting the level of consideration given to entrepreneurship in the development of the curriculum. The study adopted the content analysis approach to investigate the entrepreneurial content of textile design in the industrial design curriculum. The industrial design curriculum of the Federal University of Technology, Akure (FUTA) was selected because FUTA is the only university offering the industrial design curriculum in the region. The curriculum was analyzed across all levels, the entrepreneurial courses were highlighted based on the course synopsis while other courses were classified as general courses. The study revealed that entrepreneurship was given good consideration during the development of the curriculum. It was therefore recommended that the curriculum be updated regularly to ensure it remains relevant and meets the entrepreneurial needs of the students.